PENGEMBANGAN BAHAN AJAR MENULIS ESAI BERBASIS KONTEKS KELAS X SMA NEGERI 1 RANTAU PRAPAT - POHAN, JUSRIN EFENDI (Institut Pendidikan Tapanuli Selatan, 2018)
This research aimed to produced the module based context model of writing essay. The development of the modul model were grounded by a crucial problem, students have a low ability in writing essayby productive teaching facility or the teaching material, the teacher tend to deliver the material based on memorize context, not a synthetic thinking, so that the students fell bored and annoyed,and the teaching material was not focused in increasing students ability. Kind of this research is research and development. Research procedure used 4-D model is Define,Design, Development, and Disseminate. Module draft developed then validated by three expert judgement. After module in validated, the module stride was tested on student at class X SMA1Rantauprapat. The data obtained to be analyzed descriptively.This research found that (1) module based context of writing essay which was developed, (2) module based context of writing essay have been practice to use in writing essay leraning, and (3) module based context of writing essay have been effective in increasing student activities and motivations on studied writing learning